2022
DOI: 10.1097/fjc.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Selatogrel: A Novel Subcutaneous P2Y12 Inhibitor

Abstract: :The use of a P2Y12 inhibitor as a component of dual antiplatelet therapy in patients with an acute coronary syndrome (ACS) is well established. However, the P2Y12 inhibitors currently available have pharmacokinetic limitations due to delayed absorption, lack of enteral access for administration with oral formulations, need for intravenous access with cangrelor, or need for metabolization to be ideal in the critical 3-hour window during an ACS. Selatogrel is a novel, potent, reversible, and selective 2-phenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Selatogrel, a novel, potent, reversible, and selective 2-phenylprimdine-4-carboxamide that is subcutaneously administered is under development. The results from preclinical, phase 1, and phase 2 trials have confirmed that the agent provides sustained and reversible P2Y12 platelet inhibition with an acceptable safety profile and with a larger therapeutic window compared with the oral P2Y12 inhibitors [90,91].…”
Section: Selatogrelmentioning
confidence: 89%
“…Selatogrel, a novel, potent, reversible, and selective 2-phenylprimdine-4-carboxamide that is subcutaneously administered is under development. The results from preclinical, phase 1, and phase 2 trials have confirmed that the agent provides sustained and reversible P2Y12 platelet inhibition with an acceptable safety profile and with a larger therapeutic window compared with the oral P2Y12 inhibitors [90,91].…”
Section: Selatogrelmentioning
confidence: 89%
“…Non-nucleotide antagonists include the analogue of reactive blue 2, PSB-0739 Table 6 , [ 11 , 67 ], 6-amino-2-thio-3H-pyrimidin-4-one derivatives [ 38 ], ethyl 6-aminonicotinate acyl sulfonamides [ 8 ], flavonolignans [ 18 ], morpholine derivatives [ 3 ], piperazinyl glutamates [ 130 , 167 ], as well as salvianolic acids [ 101 ]. Selatogrel (ACT-246475) has a nanomolar affinity at the human P2Y 12 receptor [ 9 ] and can be applied by subcutaneous administration [ 14 , 147 ]. Selatogrel may act as inverse agonist at the human P2Y 12 receptor [ 132 ].…”
Section: P2y 12 Receptor Ligandsmentioning
confidence: 99%
“…We have read with great interest the article entitled ‟ Selatogrel: A Novel Subcutaneous P2Y12 Inhibitor ” by Beavers et al, 1 published ahead of print in the Journal of Cardiovascular Pharmacology. We would like to thank the authors for this important summary of the evidence on this new drug but also express concerns that they have not properly interpreted the available data regarding its safety profile.…”
mentioning
confidence: 99%